Sulphur corrosion in transformer insulating oils: its effects, detection methods, and mitigation strategies - Zulkefli, Nur Izyan Husnina; Ghani, Sharin Ab; Khiar, Mohd Shahril Ahmad; Chairul, Imran Sutan; Rahim, Nor Hidayah; Azlan, Nur Farhana Mohd (Institute of Advanced Engineering and Science, 2025)
Oil-immersed transformers are subjected to electrical, thermal, and mechanical stresses over time, which inevitably affect the insulating oil and paper insulation. The presence of sulphur corrosion also degrades the insulating oil and paper insulation. Sulphur corrosion in insulating oils has been a prevalent problem for many years, as it culminates in the failure of oil-immersed transformers. The longevity of oil-immersed transformers is dependent on the integrity of the insulating oil and paper insulation, which can deteriorate owing to sulphur corrosion. The occurrence and accumulation of copper sulphide (Cu2S) can result in transformer malfunctions, which is a significant issue for transformer manufacturers and operators. This paper provides a concise overview of the effects of sulphur corrosion, its detection methods, as well as its mitigation strategies. It is believed that this paper will enhance the understanding of sulphur corrosion in insulating oils, provide the best practices for sulphur corrosion management, and serve as guidance on enhancing transformer reliability and performance.